ANALISIS POTENSI DAN TINGKAT EKSPLOITASI ZONA PENANGKAPAN DI KABUPATEN BENGKALIS PROVINSI RIAU - Amrizal Amrizal; Sjafrizal Sjafrizal; Mahdi Mahdi; Junaidi Junaidi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research in two sub-districts and District Bantan North Rupat Bengkalis District, Riau Province. The purpose of this study was to analyze: The potential of fishery resources, the condition of waters, eklpoitasi level of fishery resources in the arrest of three zones Bengkalis. The study states that the sustainable potential of Zone I to 1287.09 tons / year. The rate of exploitation in 2013 amounted to 113.04% with the condition have been over fishing, sustainable Potential Zone II is 4444.48 tons/year and the rate of exploitation in 2013 amounted to 90.46% with very keritis conditions, sustainable Potential Zone III for 3181, 38 tons / year by the rate of exploitation in 2013 amounted to 81.67% with the condition of the waters have started critical